Conduction Slowing in Diabetic Sensorimotor Polyneuropathy - Dunnigan, Samantha K.; Ebadi, Hamid; Breiner, Ari; Katzberg, Hans D.; Lovblom, Leif E.; Perkins, Bruce A.; Bril, Vera (Diabetes care, 2013)
Mild demyelination may contribute more to the pathophysiology of nerve fiber injury in diabetic sensorimotor polyneuropathy (DSP) than previously thought. We investigated the clinical and electrodiagnostic classifications of nerve injury in diabetic patients to detect evidence of conduction slowing in DSP. Type 1 diabetic subjects (n = 62) and type 2 diabetic subjects (n = 111) with a broad spectrum of DSP underwent clinical examination and nerve conduction studies (NCS). Patients were classified as having axonal (group A), conduction slowing (group D), or combined (group C) DSP based on electrodiagnostic criteria. Patients with chronic immune-mediated neuropathies were not included. The groups were compared using ANOVA, contingency tables, and Kruskal-Wallis analyses. Of the 173 type 1 and type 2 diabetic subjects with a mean age of 59.1 ± 13.6 years and hemoglobin A1c (HbA1c) of 8.0 ± 1.8% (64 ± 19.7 mmol/mol), 46% were in group A, 32% were in group D, and 22% were in group C. The severity of DSP increased across groups A, D, and C, respectively, based on clinical and NCS parameters. The mean HbA1c for group D subjects (8.9 ± 2.3% [74 ± 25.1 mmol/mol]) was higher than for group A and group C subjects (7.7 ± 1.4% [61 ± 15.3 mmol/mol] and 7.5 ± 1.3% [58 ± 14.2 mmol/mol]; P = 0.003), and this difference was observed in those with type 1 diabetes. The presence of conduction slowing in patients with suboptimally controlled type 1 diabetes indicates the possibility that this stage of DSP may be amenable to intervention via improved glycemic control.